Exploring How Green Perceived Value and Brand Knowledge Shape Consumers Intention to Buy Eco-Friendly Products through Green Attitude - Panjaitan, Rahellia; Najib, Ahmad Khoirun; Rahayu, Gita; Shalahuddin, M. (Institute of Computer Science (IOCS), 2025)
This study examines the influence of Green Perceived Value (Functional, Conditional, Social, and Emotional Values), Green Product Knowledge, and Attitude Toward Purchasing Green Products on Purchase Intention toward Green Products among consumers in the Greater Palembang Area. Using a quantitative approach, data were collected from 200 respondents who had purchased green products, analyzed through SEM-PLS. The results show that Functional Value, Conditional Value, Emotional Value, and Green Product Knowledge positively affect Attitude Toward Purchasing Green Products, while Social Value has no significant impact. Attitude also positively influences Purchase Intention. These findings support previous studies and confirm the relevance of the Green Perceived Value (GPV) theory. The study contributes to theory and practice by highlighting the importance of emphasizing functional, emotional, and promotional benefits of green products through effective marketing communication and environmental education. Future research should expand the geographic scope and include Word of Mouth (WOM) to better understand social influences on green purchasing behavior